Exploring the Marketing Strategy of Imported Books Trading on Social Media Platforms - Aminudin Ma'ruf; Rika Septiani Puspita Sari (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2024)
Technological progress has had an impact on various fields. The economic sector has not been spared either. With the development of technology businesses, the right strategy must be embraced. This study aims to determine the marketing strategies businesses adopt in trading imported books on the Instagram platform. A qualitative research method was using interviews and documentation data. A total of six businesses were interviewed, and the data was then presented with some analysis. The results indicate that the marketing strategies used by the traders are promotions through Instagram features, market segmentation, and consumer engagement. The paper humbly suggests that businesses may widen their market by adopting other social media and involving e-commerce. In addition, the study argues that businesses must consider several factors in their promotions, such as price, quality, and trend. The paper carries some limitations and comes with several recommendations.